THE EFFECT OF CRAB SHELL ASH TO THE GROW AND YIELD OF SOYABEAN ON PEAT SOIL - Meisan .; Dwi Zulfita; Putu Dupa Bandem (Jurnal Sains Pertanian Equator, 2019)
Soybean is the third crops that have hight value of economy after rice and corn that very potential for cultivated. Crab shell ash have  importeant ruke of solving peat soils pH. This research aimed to know the best dose of crab shell ash for the grow and yield of soybean on peat soil. This research was conducted at the research feld of Agricaltural Faculty Tanjungpura University Pontianak from April 02 nd to June 30th 2019. The metod used in this research was Complete Random Design (CRD) consisted of 5 levels  of crab shell ash with 5 replications respectively and 4 sample plant. The levels of crab shell ash were (k1) 350, (k2) 437, (k3) 525, (k4) 612 and     (k5)700 grams/polybag consecutively. The observed variables were the plant height, root volume, plant dry weight, grains weight per plant, and 100 grains dry weight. The resuts showed that the levels of crab shell ash had no significant effects to the growth and yield of soybean on peat soil. The most effective levels of crab shell ash was 350 grams/polybag that was equal to 20 tons/ha. Keywords: crab sheel ash, peat, soyabean.